Термінологія в сучасній правотворчості - Василенко, В. А.; Vasylenko, V. A.; Валентина Василенко (Науковий вісник Міжнародного гуманітарного університету. Серія : Філологія. - 2019. - Вип. 43, т. 1. - С. 143-146, 2019)
Розкрито роль термінів у правотворчості. Окреслено ті розділи нормативних актів (про юридичну техніку, про мову й ін.), у яких вони зазвичай розміщуються. Розглянуто діяльність держави зі збагачення термінології законів. Наголошено, що регульовані правовими актами суспільні відносини постійно видозмінюються, диференціюються й інтегруються.

The article reveals the role of terms in legislative process. Those sections of regulatory acts (on legal technique, language etc), where these terms can be found, are mentioned. The government activity as for enriching terminology of laws is concerned. It is underlined that social relations regulated by the legal acts is constantly changing and integrating. The author defines the sources of legislation terminology (dictionaries), genesis and development of terminology. It is emphasized that classifying definitions we should distinguish scientific terms that have approached as much as possible to the sense which these terms are devoted to. The influence of society on terms’ development is underlined. It is determined that science and technologies create new approaches to the interpretation of terms combinations because terminology is sometimes aimed at characterizing, understanding, analyzing and learning the lexical item itself which is considered as a whole. On the basis of the analysis we defined that the scientific interpretation of correlation between language and law influences the final outcome of interrelation of certain events in society’s life, particularly the definition of terms’ role which intermediate this interrelation. The article states that scientific content of the term and its legislative content are not identical. That’s why the most annexes to codes and laws concern those articles that reveal the content of terms, definitions and categories used in it. These terms, definitions and categories are becoming more various because they encompass many characteristics and peculiarities that were brought out in the process of modern development of science, technology, practical use and application. The questions of criteria and typology (formational, civilizational) of terminology, importance of improving law language for the development of legislation and its realization are considered. The question of the need of special terminological system use in the process of legislation formulation is still controversial among the researchers in the sphere of legislative technique. As a result of it we made a conclusion that legislation is constantly being enriched by such useful and necessary attribute as developed terminology which is getting more and more complicated and performs a lot of functions.

Раскрыта роль терминов в правотворчестве. Обозначены разделы нормативных актов (о юридической технике, о языке и др.), в которых они обычно размещаются. Рассмотрена деятельность государства по обогащению терминологии законов. Отмечено, что регулируемые правовыми актами общественные отношения постоянно видоизменяются, дифференцируются и интегрируются.
Terminology in modern legislative process
Keywords: правотворчість; термінологія; юридична техніка; норма права; мова закону; law making; terminology; legal technique; rule of law; language of the law; правотворчество; терминология; юридическая техника; нормы права; язык закона